Isolamento e identificação de substâncias com ação espasmolítica de folhas de Lippia thymoides Mart. & Schauer (Verbenaceae) - Magalhães, Acsa Oliveira (2018)
Lippia thymoides, commonly known as “alecrim-do-campo” or “alecrim-do-mato”, belongs to the Verbenaceae family. This specie is found in the states of Bahia and Minas Gerais being used in folk medicine by their population. The aim of this work was to isolate and identify compounds of dichloromethane fraction from L. thymoides leaves and to evaluate their in vitro spasmolytic activity. The leaves were collected at the Feira de Santana (Bahia), grinded and extracted with methanol. The crude extract (LTB) fractionation was performed using liquid-liquid partition to obtain the hexane, dichloromethane (LTD) and ethyl acetate fractions. Dichloromethane fraction was sub fractioned by column chromatography. Isolated compounds (one triterpene, a mix of two phytosterols and six flavonoids) were analyzed by 1H and 13C RMN and compared with literature data for structure elucidation. 3,5-dihydroxy-7,4'-methoxyflavolol; 7,4’-dimitylaromadendrin; rhamnocitrin; eupalitin; mixture of hispidulin and jaceosidin; α-amirin; and the mixture of β-sitosterol and stigmasterol were isolated. The spasmolytic activity of LTB, LTD and isolated compounds was tested in Cavia porcellus removed trachea. The mix of flavones [(CE50 = 15,19 µg/mL (12,86 – 17,93)] showed the highest spasmolytic activity reaching the Emax of 100% at a concentration of 81 µg/mL. The results demonstrate that L. thymoides is a potential source of bioactive compounds with strong actionrelaxing on the smooth muscle of trachea isolated from guinea pig.